1, 2-Propanediol-linked chiral symmetric and non-symmetric liquid crystal dimers containing trifluoromethyl. Issue 12 (25th September 2016) - Xu, Zhi-Xin; Yao, Miao; Feng, Wei-Jiao; Liu, Kun-Li; Zhu, Qi; Tian, Mei; Hu, Jian-she; Yao, Dan-Shu
ABSTRACT: Four symmetric and non-symmetric chiral liquid crystal dimers containing trifluoromethyl groups, termed asTFBA-PD-TFBA, UEBBA-PD-TFBA, UEBA-PD-TFBA andUEA-PD-TFBA, respectively, have been synthesised and characterised.UEA-PD-TFBA exhibited chiral nematic phase, whereas the other three dimers displayed chiral smectic A phase. X-ray diffraction (XRD) has revealed the structure of the smectic A phase forTFBA-PD-TFBA to be intercalated, whereas that forUEBBA-PD-TFBA andUEBA-PD-TFBA to be monolayer and interdigitated, respectively. In addition, the weaker peak corresponding to a shorter layer spacing was observed forUEBBA-PD-TFBA andUEBA-PD-TFBA . Considering the results of XRD measurements and computer simulations, the structural model corresponding to the shorter layer spacing is assigned as horseshoe-like shape. The absence of smectic behaviour forUEA-PD-TFBA reveals that the weaker aromatic–aromatic interactions cannot stabilise the smectic A phase. GRAPHICAL ABSTRACT: